Veterinary Drug Use Pattern in livestock and Its Public Health Significance, Gondar Town Veterinary Clinic, Northern Ethiopia - Mekoya, Teklu Yitbarek; Fentahun, Selamawit (Food, Agriculture and Natural Resources - NETWORKS, 2024)
A cross-sectional and retrospective study design and simple random sampling strategy was conducted in Gondar town veterinary clinic, northern Ethiopia with the aim of evaluating drug use pattern and show public health significance of irrational veterinary drug use. A total of 2117 drugs were prescribed to 1717 veterinary patients randomly selected from the case registry in this study. The result indicates average number of drugs prescribed per case was 1.23 and the maximum of three drugs was prescribed. The percentages of antimicrobial, anthelmintic, endectocide and other drugs prescribed were 1182 (55.7%), 481 (22.7%), 426 (20.1%), and 28 (1.3%), respectively. All patients were treated without correct laboratory support. As a result, antimicrobials were inappropriately prescribed in 1.4% of viral diseases, 0.2% of external parasitic diseases, 0.8% of internal parasitic diseases, 0.3% of metabolic diseases, 0.1% of fungal diseases, and anthelmintics in 0.1% of bacterial diseases and 0.5% of external parasitic diseases. 2013/2117 (95.1%) the route of administration of the prescribed drugs was not stated. Clinic professionals were 80% animal health assistants and 20% veterinarians. The results reveal problems with correct diagnosis, low level of education of prescribers, few essential drugs, absence of standard veterinary drug lists, and inappropriate drug use; these all principals to public health significance. Therefore, the availability of key essential drugs should improve and available drugs be prescribed with its appropriate doses, routes, and regimens. Veterinarians should be made aware of the irrational use of veterinary drugs and their public health implications.